BIFUNCTIONAL Bi2O3/ZrO2 CATALYSTS FOR SYNTHESIS OF THIRD GENERATION BIODIESEL FROM NANNOCHLOROPSIS SP. LIPID - ABD RAHMAN, NURUL JANNAH (2021)
Microalgae as third generation biofuel have been found to simplify the shortcomings experienced by its predecessors. However, high free fatty acid content represents the major limitation which requires the microalgae lipid to undergo a two-step process to produce biodiesel. As an alternative, in this study, bifunctional Bi2O3/ZrO2 catalysts were developed for simultaneous esterification–transesterification of Nannochloropsis sp. lipid to biodiesel. First, ZrO2 was synthesized using precipitation, sol-gel, hydrothermal and surfactant assisted hydrothermal methods, dried at 120 °C and calcined at 500 °C. The selected ZrO2 was further impregnated with 5–15 wt.% Bi2O3 loadings using incipient wetness impregnation method, dried at 120 °C followed by calcination at 500 °C.